Ge(1-x) Mn(x) clusters: central structural and magnetic building blocks of nanoscale wire-like self-assembly in a magnetic semiconductor. - Bougeard, D; Sircar, N; Ahlers, S; Lang, V; Abstreiter, G; Trampert, A; Lebeau, J; Stemmer, S; Saxey, D; Cerezo, A (2009)
Controlled nanoscale self-assembly of magnetic entities in semiconductors opens novel perspectives for the tailoring of magnetic semiconductor films and nanostructures with room temperature functionality. We report that a strongly directional self-assembly in growth direction in Mn-alloyed Ge is due to a stacking of individual Ge(1-x)Mn(x) clusters. The clusters represent the relevant entities for the magnetization of the material. They are formed of a core-shell structure displaying a Mn concentration gradient. While the magnetic moments seem to be carried by the shells of the clusters, their core is magnetically inactive.